Credibility and scale as barriers to uptake and use of seasonal climate forecasts in Bobirwa Sub-District, Botswana - Selato, Janet Chatanga (Department of Environmental and Geographical Science, 2018)
Seasonal climate forecasts (SCF) can play a crucial role in reducing vulnerability to climate variability, particularly for rural populations reliant on agriculture for their livelihood. The use of disseminated SCF by farmers in decision-making could reduce losses and maximise benefits in agriculture. Despite the potential usefulness of SCF, incorporating them into farming decisions is a complex process that navigates through several barriers which constrain their effective use. The first two barriers, namely credibility (trust on SCF) and scale (relevance of SCF in geographical space and time), originate from the limitations of SCF associated with the form in which they are produced. In this study, credibility and scale are investigated as limitations of SCF, which potentially bar the uptake and use of SCF in Bobirwa sub-district. The second group of barriers are beyond the SCF themselves but limit their effective use and emanate from biophysical, socio-cultural and economic factors. This study examines whether credibility and scale are barriers to the use of SCF in Bobirwa farmers' decision-making, investigates how SCF are used in decision-making, and seeks to find out how the barriers are overcome. To make these investigations, qualitative data was collected from subsistence agro-pastoral farmers in eight villages in Bobirwa sub-district of Botswana using semi-structured interviews. Data was collected considering gender to allow for gendered analysis. Themes related to the main study questions were identified from the data and analysed for the number of people who mentioned the themes. It was found that all 47 farmers interviewed coincidentally had access to SCF and the majority used SCF in their decision-making, while only a handful of farmers were non-users of SCF. The results show that scale (both temporal and spatial) is a barrier for users of SCF, whereas credibility is a major constraint for non-users of SCF in Bobirwa. To cope with the barriers, farmers mainly use local knowledge to complement SCF. Additionally, farmers apply advice from Ministry of Agriculture (MoA) and use economic information in their decisions to deal with the barriers. Despite the barriers, some farmers indicated that using SCF was beneficial in increasing harvests, providing warnings and minimising losses of crops and livestock. However, disadvantages of using SCF were also highlighted, including lost crops, seeds and harvest, and missed opportunities to plant because of lack of temporal and geographical detail in the forecasts. The barrier of credibility has contributed to a few non-users resorting to using traditional planting, possibly making them vulnerable to the impacts of climate variability. A gendered analysis shows that almost equal proportions of both males and females use SCF. Moreover, women use SCF for crop farming while men use it for livestock management, which is aligned to traditional roles in Botswana. It is also revealed that, unlike women who only use local knowledge and MoA advice to overcome SCF limitations, a few men also use economic ventures, which could make men less vulnerable than women farmers. Strong networks between scientists and farmers can reduce the perceived credibility barrier, and innovative ways of reducing the scale barrier can be devised. Therefore, recommendations from the study include continuous engagement with farmers to understand their decisionmaking context in order to tailor the information to their local context as much as science permits. Government programmes should be designed to integrate SCF to build farmers' resilience to climate variabilities. The impacts on livestock farming, which is dominated by men, need to be given as much prominence in SCF information as arable farming. Forecasters should continue to improve credibility and scale without compromising either factor to avoid chances of contributing to the vulnerability of farmers particularly women, who mostly rely on SCF for crop production.